Micromorphological study of Cyperaceae flora from southwestern Nepal (Botanica Orientalis: Journal of Plant Science, 2025)
The value of micromorphological characters as a practical guide for the taxonomic study of the members of the family Cyperaceae is indisputable. The arrangement of glumes, style structure, and nutlet characteristics of 9 genera and 46 species of the family Cyperaceae collected from the Kanchanpur District, in the southwestern Tarai region of Nepal were investigated using a stereo zoom microscope to ascertain the taxonomic utility of these characters in differentiating closely related genera and species. The studied taxa included representatives of the genera Actinoscirpus (Ohwi) R.W.Haines & Lye, Bolboschoenus (Asch.) Palla, Bulbostylis Kunth, Carex L., Cyperus L., Eleocharis R.Br., Fimbristylis Vahl, Schoenoplectiella Lye, and Scleria P.J.Bergius. Among the micromorphological characters, the nutlets displayed considerable diversity in shape, size, color, and surface features, making these characters valuable for delimiting taxa within the family Cyperaceae. This study highlights the significance of nutlet morphology as a powerful tool in Cyperaceae taxonomy, emphasizing its value in supporting systematic research. The diversity of nutlet characteristics among the studied taxa is illustrated with detailed photographs taken during the study.